The evolving role of multi-modality imaging in transcatheter tricuspid valve interventions - Gheorghe, Livia Luciana; Hegeman, Romy; Vrijkorte, Martijn; Wunderlich, Nina; Cavalcante, Joao; Wang, Dee Dee; Rana, Bushra; Vannan, Mani; Timmers, Leo; Swaans, Martin (Frontiers in Cardiovascular Medicine, 2022)
Tricuspid valve pathophysiology is not well-understood. Emergence of novel transcatheter tricuspid therapies has fueled the requirements for improved imaging visualization techniques and interventional imaging physician skillsets in guiding these complex transcatheter procedures. There is growing understanding on the clinical significance of tricuspid regurgitation which expanded the interest for percutaneous tricuspid valve interventions. The present review concentrates on three essential aspects of tricuspid valve pathophysiology: anatomical considerations for tricuspid interventions, optimal timing of tricuspid interventions by imaging guidance, and the role of interventional imaging physicians’ skillset and knowledge in this field.